Os desgarrados do campo : texto e contexto na obra de Charles Kiefer - Scalabrin, Leandro Gaspar (2011)
This dissertation analyzes three works of writer Charles Kiefer from the hypothesis that they compose a trilogy: O pêndulo do relógio (1984), Valsa para Bruno Stein (1986) and Quem faz gemer a terra (1991). To do so, it identifies, in each one of them, thematic (the social matter), compositional (typical personages, surroundings, time and plot) and aesthetic elements (traces of realism) common and connected between them. Besides, proceeds the identification of the social context represented and it is verified its application as agents of its structure, trying to accomplish a full dialectical interpretation between text and context. In the thematic analyzes of the works, it is used the reflections of Antonio Candido about critic and sociology, as well as the concept of typical personage and the typicality of Marxist trends of the theory of literature in the analyzes of the compositional elements. The considerations about realism are based on the works of Georg Lukács, Frederic Jameson, Alfredo Bosi, Ana Cotrim, Celso Frederico and Leandro Konder. The main finding at the end of the research is that the works mentioned above are connected among themselves by a thematic unit that represents the social and economical transformations due to the modernization of agriculture in the plateau of Rio Grande do Sul, the changes in the patriarchal families and the migration from the fields to the cities between 1960 and 1990. It was also identified the presence of the personage Hermann Hauser in the three works, from the Müllers, in the first and in the last, and the landless farmers in the second and third works. It was also verified that the typical personages and the conception that art is a way of knowledge of reality are the traces of realism present in the trilogy of the stray from the fields